Cicada summer - Beaty, Andrea (Amulet Books : Scholastic, Inc., 2010)
Twelve-year-old Lily, believing she could have prevented the accident that caused her brother's death, has quit speaking leaving everyone to think that she is brain damaged, but in her silence she sees everything, and when sly newcomer Tinny comes to town, Lily suddenly has a lot to talk about--if only she can make herself speak the words.